Genes Involved in Oxidative Stress Pathways Are Differentially Expressed in Circulating Mononuclear Cells Derived From Obese Insulin-Resistant and Lean Insulin-Sensitive Individuals Following a Single Mixed-Meal Challenge - Baig, Sonia; Parvaresh Rizi, Ehsan; Chia, Chelsea; Shabeer, Muhammad; Aung, Nweni; Loh, Tze Ping; Magkos, Faidon; Vidal-Puig, Antonio; Seet, Raymond C. S.; Khoo, Chin Meng; Toh, Sue-Anne (Frontiers in Endocrinology, 2019)
Abstract Background: Oxidative stress induced by nutritional overload has been linked to the pathogenesis of insulin resistance, which is associated with metabolic syndrome, obesity, type 2 diabetes and diabetic vascular complications. Postprandial changes in expression of oxidative stress pathway genes in obese versus lean individuals, following intake of different types of meals varying in macronutrient composition have not been characterized to date. Here we aimed to test whether/how oxidative stress responses in obese versus lean individuals are modulated by meal composition. Methods: High-carbohydrate (HC), high-fat (HF) or high-protein (HP) liquid mixed meals were administered to study subjects (lean insulin-sensitive, n=9 and obese insulin-resistant, n=9). Plasma levels of glucose and insulin, lipid profile, urinary F2-isoprostanes (F2-IsoP) and expression levels of genes of oxidative stress pathways were assessed in mononuclear cells (MNC) derived from fresh peripheral blood, at baseline and up to 6-hour postprandial states. Differences in these parameters were compared between insulin-sensitive/resistant groups undergoing aforementioned meal challenges. Results: Obese individuals exhibited increased pro-oxidant (i.e. CYBB and CYBA) and anti-oxidant (i.e. TXN RD1) gene expression in the postprandial state, compared with lean subjects, regardless of meal type (P interaction for group × time<0.05). By contrast, lean subjects had higher expression of NCF-4 gene (pro-oxidant) after HC meal and SOD1 gene (anti-oxidant) after HC and HF meals (P interaction for group × meal<0.05). There was an increase in postprandial level of urinary F2-IsoP in the obese (P<0.05) but not lean group. Conclusions: These findings may represent an adaptive oxidative response to mitigate increased stress induced by acute nutritional intake. Further, the results suggest an increased predisposition of obese subjects to oxidative stress. Chronic nutritional excess resulting in increases in body weight and adiposity might lead to decompensation leading to worsening insulin resistance and its sequel. Insights from this study could impact on nutritional recommendations for obese subjects at high-risk of cardiovascular diseases.